Os três momentos pedagógicos como estruturantes de currículos - Araújo, Laís Baldissarelli de (2015)
The present research is classified as a qualitative impression research. With its development we tried to deal the three pedagogical moments use (3PM) as structurants curriculum, showing that the use of this dynamics doesn t restrict to a didactic- pedagogical tool for the classroom. It has the problem research: Whats are the challenges and potentialities found for teachers of a state public school from Santa Maria/RS to use the 3PM dynamic to curricular organization and also as didactic-pedagogical tool in the classroom? In this project, the 3 PM were used in the curriculum structuralization of the state school of basic education, Luiz Guilherme do Prado Veppo State Institute. From this investigation problem lined the goals, being: developing through of a formative and collective process with the teachers of the school, the programmatic sequence of the science area curriculum through the 3PM use. Evaluate the challenges and potentialities found for the teachers during the formative process about the dynamic adoptive and examine the potentialities and resistances about the accomplished investigation to get the theme through the 3PM dynamic, like also its implementation in the classroom. The used tools to collect the information were: questionnaire, pedagogic practice diary of the participant teachers, researcher s diary, semi-structured interviews with students and teachers and documental test of the classes planning. The theoretical referentials which built this dissertation are backed up in the Freireanos assumptions, thematic approach and in the 3PM as structurants of school curriculums. The methodology to analyse the data was the discursive textual analysis, emerging of this process two categories : the formative process, the implementation of the classes in the 3PM perspective: some potentialities and the formative process and the implementation of the classes from the 3PM dynamic: challenges to be faced. In the potentialities grouped characteristics like: participation, interest and the built dialogue between teachers and students. In this category still were examined the teacher s views about the 3PM use during the development of the course and also in the classroom, standing out the importance indicated by the teachers of the formative process. In the challenges category, we can find the disadvantages which were present during the range, as being the teacher s attitudes, and sometimes, they made it difficult the development of the collective and interdisciplinary project. In addition, the faced difficulties are indicated about the work conditions and the reflex caused for the formation presented by the teachers during the offered activities.